2007
DOI: 10.5194/acp-7-6061-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects on surface atmospheric photo-oxidants over Greece during the total solar eclipse event of 29 March 2006

Abstract: Abstract.This study investigates the effects of the total solar eclipse of 29 March 2006 on surface air-quality levels over Greece based on observations at a number of sites in conjunction with chemical box modelling and 3-D air-quality modelling. Emphasis is given on surface ozone and other photooxidants at four Greek sites Kastelorizo, Finokalia (Crete), Pallini (Athens) and Thessaloniki, which are located at gradually increasing distances from the path of the eclipse totality and are characterized by differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…4, where the structure of the ABL is stable all the time from 09:20 to 10:10 BJT. As reported by Eaton et al, during the maximum phase of an eclipse, the sensible heat and radiation fluxes are affected, turbulence is reduced, and the air refractive index structure constant is dramatically decreased [9,10] This resembles the phenomenon recorded during nighttime where the residual layer coexists with the nocturnal boundary layer.…”
supporting
confidence: 55%
“…4, where the structure of the ABL is stable all the time from 09:20 to 10:10 BJT. As reported by Eaton et al, during the maximum phase of an eclipse, the sensible heat and radiation fluxes are affected, turbulence is reduced, and the air refractive index structure constant is dramatically decreased [9,10] This resembles the phenomenon recorded during nighttime where the residual layer coexists with the nocturnal boundary layer.…”
supporting
confidence: 55%
“…In the same event, the partitioning of NO x between NO and NO 2 was determined almost exclusively by variations in J NO 2 (Fabian et al, 2001). More recently in the total solar eclipse of 29 March 2006, observations and modeling show that there was a significant decrease in O 3 and NO and an increase in NO 2 at polluted sites, but no clear impact on these pollutants at unpolluted sites (Zanis et al, 2007). The decrease in the surface ozone concentration that was observed after the beginning of the eclipse lasted two hours, probably due to the decreased efficiency of photochemical ozone formation (Tzanis et al, 2008).…”
mentioning
confidence: 92%
“…Similar conclusions were derived in a comparison of eclipse data from four sites in Greece. At two relatively unpolluted sites there was no clear signal in O 3 , NO, and NO 2 , while at two urban sites, decreases in O 3 and NO, and an increase in NO 2 (Zanis et al, 2007) were observed. Evidently, under eclipse conditions, in environments with higher NO x emission, there is a higher rate of NO x buildup from the loss of turbulent mixing, increase in NO 2 from the NO + O 3 -> NO 2 reaction, and conversely a higher rate of O 3 loss.…”
Section: Factors Driving the Trace Gas Behavior On The Eclipse Daymentioning
confidence: 78%